THE KONYA SCHOOL OF PHILOSOPHY AS A HISTORICAL FRAMEWORK OF OTTOMAN THOUGHT - Acikgenc, Alparslan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
THE KONYA SCHOOL OF PHILOSOPHY AS A HISTORICAL FRAMEWORK OF OTTOMAN THOUGHT